Chunking Techniques to Enhance Learning Outcomes in the Human Body System - Satwika Trianti Ngandoh; Riandi Riandi; Adi Rahmat; Muslim Muslim; Emilia Candrawati; Muhammad Dirham (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: Chunking is a cognitive method that breaks down complex material into smaller, more digestible pieces, improving comprehension and retention of knowledge. This study aims to assess the efficacy of the chunking strategy in improving student learning outcomes for human body system materials. Method: The research method was quasi-experimental with a post-test control group design. The research subjects of eighth-grade students consisted of experimental and control classes. The instrument used was a multiple-choice test to understand the concept of human body systems. Results: The study showed that the chunking technique effectively improved learning outcomes because it helped the brain process information better. The chunking technique increases students' understanding of the human body system's material, which impacts better learning outcomes. Novelty: This study introduces the chunking technique as a strategy in science learning, especially in understanding the material of the human body system. The chunking technique helps teachers present learning that suits the needs of students. The application of chunking techniques in learning, assisted by learning media, can accommodate the differences in student characteristics in class.